APPLICATION OF LEARNING GUIDANCE TO IMPROVE SELF-CONCEPT OF STUDENTS - Clara Fransiska Dora; Bambang Sahono (UNIB Press, 2018)
The purpose of this study was to describe the application of group guidance and describe the effectiveness of the implementation of group guidance on the Self Concept of class VIII students at SMP 1 Talang Padang. The research method used was classroom action research and quasi-experimental. While the research subject is students of class VIII semester one of the 2018/2019 school year in SMP Negeri 1 Talang Padang. For the 15 class action research while for the quasi experiment 30 people. For quasi-experiments, these were divided into two groups, namely, 15 experimental groups and 15 control groups. Data collection techniques in this study used group guidance observation sheets, self concept observation sheets, this shows self-concept and learning achievement increased. The conclusion of this study is that the application of group guidance can improve self-concept.